Alteration at the Olympic Dam IOCG–U deposit: insights into distal to proximal feldspar and phyllosilicate chemistry from infrared reflectance spectroscopy. Issue 8 (16th November 2016) - Mauger, A. J.; Ehrig, K.; Kontonikas-Charos, A.; Ciobanu, C. L.; Cook, N. J.; Kamenetsky, V. S.
ABSTRACT: Twenty thousand metres of diamond drill core representing a 14 km cross-section from weakly to intensely altered Roxby Downs Granite through the Olympic Dam Breccia Complex, host to the Olympic Dam iron-oxide–copper–gold–uranium deposit in South Australia, was analysed using the HyLogger-3 spectral scanner. Thermal and shortwave infrared spectroscopy results from 30 drill holes provide insight into the spatial relationships between quartz, orthoclase–microcline, albite–oligoclase and progressively changing sericite and chlorite compositions. The relative proportions of quartz, feldspars and phyllosilicates were mapped with thermal infrared spectroscopy. Variations in the chemistry of sericite and chlorite were extracted by proxy from their shortwave infrared spectral response, together with their relative spatial distribution. HyLogger scanning has revealed four deposit-scale mineralogical trends, progressing from least-altered Roxby Downs Granite into mineralisation where most of the feldspar has been replaced by sericite + hematite + quartz: (1) a progressive Al–OH wavelength shift of 2205 nm to 2210 nm for sericite, followed by a spatially rapid reversal corresponding to lower phengite/muscovite abundance ratios; (2) progressive Mg/Fe–OH wavelength shift of 2248 nm to 2252 nm reflecting an increase in the Fe:Mg ratio of chlorite; (3) increasing ratio of microcline to orthoclase followed by a rapid decrease; and (4) slightly decreasing ratio of albite to oligoclase followed by plagioclase destruction prior to albite replacement by sericite. The HyLogger feldspar results support recent petrographic evidence for hydrothermal albite and K-feldspar at the Olympic Dam deposit, not previously reported. The spectral results from continuous HyLogger scans also show that the microscopic observations and proposed feldspar replacement reactions are not locally isolated phenomena, but are applicable at the deposit and regional-scale. A modified quartz–K-feldspar–plagioclase ternary diagram utilising mineralogy interpreted from HyLogger thermal infrared spectra (QAPTIR ) diagram along with supporting data on the abundance ratios of orthoclase/microcline and albite/plagioclase, and the wavelength shifts in characteristic absorption features for sericite and chlorite, can be used as empirical vectors towards mineralisation within the Olympic Dam mineral system, with potential application to other IOCG ore-forming systems. Intrusion of Gairdner Dyke Swarm dolerite dykes into sericite ± hematite altered Roxby Downs Granite results in retrograde albite–chlorite–magnetite alteration envelopes (up to tens of metres thick) overprinting the original sericite ± hematite alteration zone and needs to be carefully evaluated to ensure that such areas are not falsely downgraded during exploration.